2021
DOI: 10.1038/s41467-021-27233-4
|View full text |Cite
|
Sign up to set email alerts
|

A H2O2-activatable nanoprobe for diagnosing interstitial cystitis and liver ischemia-reperfusion injury via multispectral optoacoustic tomography and NIR-II fluorescent imaging

Abstract: Developing high-quality NIR-II fluorophores (emission in 1000–1700 nm) for in vivo imaging is of great significance. Benzothiadiazole-core fluorophores are an important class of NIR-II dyes, yet ongoing limitations such as aggregation-caused quenching in aqueous milieu and non-activatable response are still major obstacles for their biological applications. Here, we devise an activatable nanoprobe to address these limitations. A molecular probe named BTPE-NO2 is synthesized by linking a benzothiadiazole core w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
60
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(61 citation statements)
references
References 70 publications
1
60
0
Order By: Relevance
“…The recently emerging second NIR (NIR-II, 1000–1700 nm) window exhibits great promise for bioapplications as it possesses significantly reduced light–tissue interaction and enables large-depth and high-resolution imaging in a living body [ 122 , 123 , 124 , 125 , 126 ]. Zhao and Wu et al reported on a H 2 O 2 -activatable AIE nanoprobe for sensitive disease diagnosis via NIR-II fluorescence and PA imaging [ 127 ]. As displayed in Figure 7 , the low-bandgap D-A compound consisted of two TPE groups that would result in AIE feature and increased conjugation, and two nitrophenyloxoacetamide moieties that could be cleaved in the presence of H 2 O 2 .…”
Section: Detection Of Reactive Oxygen Nitrogen Speciesmentioning
confidence: 99%
“…The recently emerging second NIR (NIR-II, 1000–1700 nm) window exhibits great promise for bioapplications as it possesses significantly reduced light–tissue interaction and enables large-depth and high-resolution imaging in a living body [ 122 , 123 , 124 , 125 , 126 ]. Zhao and Wu et al reported on a H 2 O 2 -activatable AIE nanoprobe for sensitive disease diagnosis via NIR-II fluorescence and PA imaging [ 127 ]. As displayed in Figure 7 , the low-bandgap D-A compound consisted of two TPE groups that would result in AIE feature and increased conjugation, and two nitrophenyloxoacetamide moieties that could be cleaved in the presence of H 2 O 2 .…”
Section: Detection Of Reactive Oxygen Nitrogen Speciesmentioning
confidence: 99%
“…The strongly electron-donating carbazole unit and p-bridge of the thiophene group can realize strong intramolecular charge transfer (ICT) for red-shied emission in the NIR region, thus reducing the interference from background biological uorescence for precise imaging. [31][32][33][34] The hydrophilic pyridinium salt group can maintain good miscibility of TCM-CPS in biological media, thus achieving desirable "off-on" uorescence. Given that the pyridinium salt group and three cyano groups are very strong electron-withdrawing groups, the strong donor-p-acceptor (Dp-A) character of TCM-CPS can greatly separate the HOMO-LUMO distribution to decrease DE ST , thereby enhancing the intersystem crossing process (ISC) for higher ROS generation.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with these methods, fluorescent probes are extremely attractive because of their simple operation, high sensitivity, non-destructive analysis, and good compatibility with biological samples. 21–28 So far, various fluorescent probes for detecting H 2 S have been developed based on different fluorophores, such as rhodamine, 29 coumarin, 30 1,8-naphthalimide 31 and BODIPY. 32 However, the application of these probes in vivo is unsatisfactory because they have short emission wavelengths (<600 nm), resulting in high background signals and low tissue penetration.…”
Section: Introductionmentioning
confidence: 99%